Assessment of Associated Factors and Complications for Women with Poly Cystic Ovarian Syndrome in Baghdad City (Medico Legal Update, 2021)
Objectives: To assess the associated factors and complication for women with poly cystic ovarian syndrome.Methodology: A descriptive study conducted on purposive sample of (65) women whom attended Hospitalsin Baghdad city suffering polycystic ovarian syndrome for the period of (20th October 2019 through 25thFebruary 2020). Descriptive & Inferential statistical analyses were used to analyze the data.Results: The highest percentages (50%) in age group were (19-22) years, primary schools graduates,housewife, from “urban area”, with irregular cycle. Take high grains, fat, sugar in their food And sufferedfrom obesity, hirsutism, acne,amenorrhea, infertility among short term complication.Conclusions: The study concluded that there is significant relationship between occupation, body massindex, food consumption, dietary habits, environmental factors, with short term complication of PCOS.Recommendations: Need to developed training program to upgrade their knowledge and skills about healthyfood and life style to reduction the complication of PCOS.